Sentidos da diversidade sexual entre estudantes de Medicina - Silva, Maria Carolina Buiatti Amaral e (2014)
The health professional has been increasingly challenged to comply with needs of an extremely multiple and diverse population. The public policies in health area for the specific population of Lesbians, Gays, Bisexuals, Transgender (GLBT) come to assure that the access is done equitable, besides promoting the education of the professionals and face possible discrimination situations. In what concerns this population health-disease process, their specificity must be considered by the professionals for an effective treatment. This research s objective is to comprehend the meaning of sexual diversity among medicine students and its implications for this population s treatment. Five audio-recorded meetings were realized with eight medicine students, with sexuality and health formation related themes. The data analysis, grounded on social constructionism, identified the produced senses and allowed a thought about its production based on area s literature. From this analysis were selected six patches of conversations that approached questions referring to: a) Homophobia of some sexual morality; b) Talking about sexual identity and lesbianism; c) The presumed stability of the sexual identities and the bisexuality; d) The heteronormativity related to the patient; e) What needs in health?; f) The application of GLBT public policies and the medic curriculum. Overall, the results reaffirm the urgent need to improve the professional capacitation and future health professionals about sexuality, gender and sexual identity, as in graduation curriculums, too few is taught about sexuality dimensions in the doctor-patient relationship. In addition, homophobia and gender standard stimulating speeches were identified, condemning the heterosexual standard deviation and raising the question of how it could be taken to the treatment of a GLBT patient. There are many changes needed in professional formation to actualize the GLBT policies. New research about this theme is necessary to discuss not only the formation of this professional that will attend the LGBT patient, but also the necessary process to actualize policies for a better attending of health and the reduction of discriminatory process.